Application of multiregion model to EM scattering from a dielectric target above or below a dielectric rough surface. Issue 2 (2nd April 2016) - Wei, Yiwen; Guo, Lixin
Abstract: This paper is aimed at applying the multiregion model to the composite EM scattering from a dielectric target and a dielectric rough surface. In the multiregion model, the rough surface is divided into multiple regions, the method of moment (MoM) is only adopted in the dominant region. Hence, this model can markedly reduce the number of unknowns. Firstly, we derived the single integral equation (SIE) in which the number of unknowns is half of those in the conventional MoM and the equations will be easier to deal with. Then the multiregion model is extended by SIE. With the multiregion model, one can obtain the accurate equivalent currents on the dominant region and accurate bistatic scattering coefficient in small and moderate scattering angles with much less time and memory requirement.